Immunotherapy for metastatic prostate cancer: immuno-cold or the tip of the iceberg?. Issue 6 (November 2017) - Laccetti, Andrew L.; Subudhi, Sumit K.
Abstract : Purpose of review: Metastatic castration-resistant prostate cancer is in critical need of new and innovative treatment strategies. Since the approval of sipuleucel-T, the investigatory climate of prostate cancer immunotherapy has been rapidly evolving with promising developments in vaccine and immune checkpoint therapies. Recent findings: Sipuleucel-T remains the first and only therapeutic cancer vaccine approved for its survival benefit in metastatic castration-resistant prostate cancer. Additional cancer vaccines are currently being evaluated, with the most promising being a peptide vaccine encoding prostate-specific antigen, known as prostate-specific antigen-TRICOM. Emerging data supports combinatorial strategies for vaccine therapy and a potential role for implementation in earlier stages of advanced disease. Immune checkpoint therapies have demonstrated limited success in prostate cancer with negative late phase trials for ipilimumab monotherapy and discouraging early phase results for programmed cell death protein 1 blockade. Novel immune-modulatory targets and rational combination strategies aim to produce more favorable results. Recent progress has been made to determine biologic predictors for response and toxicity in prostate cancer immunotherapy aiming to improve patient selection and safety. Summary: Steady progress is anticipated in the field of prostate cancer immunotherapy including ongoing development of novel cancer vaccines, immune checkpoint therapies, and combinatorial strategies.